Differential effects of whole blood heat treatment on the ex vivo inflammatory profile of untrained and trained men. (June 2021) - Dorneles, Gilson P; Reiter, Keli C.; dos Passos, Aline; Marmett, Bruna; da Silva, Igor M.; dos Santos, Maeli A.L.; Krause, Maurício; Peres, Alessandra; Romão, Pedro R.T.
Highlights: Heating lowered the NF-κB signaling in CD14+ monocytes in untrained and trained men. The frequency of CD14-CD16+ monocytes increased after heat treatment in untrained group. Heating increased CD14+CD16- and CD14+CD16+ monocytes in untrained group. Lower CD4+CD39+ T-cells after heat exposure in whole blood of untrained men. Training status modulates acute inflammation to endotoxin challenge during heating. Abstract: This study evaluated the effects of heat stress on the ex vivo inflammatory profile in untrained and trained men. Whole blood samples from untrained (UT) and trained (TR) individuals were incubated for 2 h at 37 °C or 40 °C. The whole blood of a subsample of the participants (n = 5 in both TR and UT groups) were stimulated with lipopolysaccharide (LPS, 10 ng/mL) concomitant to heat treatment (37 °C versus 40 °C). Flow cytometry was used to assess the intracellular NF-κB activation in CD4+ T cells and CD14+ monocytes, the expression of Toll-Like Receptor-4 (TLR-4), the frequencies of CD4+CD25-CD39+ and CD4+CD25+CD39+ T cells and monocyte subsets (CD14+CD16-; CD14+CD16+; CD14-CD16+), the mitochondrial membrane potential (MMP) and the reactive oxygen species (ROS) production by lymphocytes and monocytes. The production of interleukin (IL)-6, IL-10, and tumor necrosis factor-alpha (TNF-α) by LPS-stimulated whole blood were also evaluated. Heat treatment (40 °C) increased the proportions of CD14+CD16- and CD14+CD16+ monocytes and the lymphocyte MMP in the UT group. The frequencies of CD14-CD16+ monocytes and the activation of NF-κB in CD14+ monocytes decreased in UT and TR groups after heat treatment, while a reduction in CD4+CD25-CD39+ T-cells was observed only in the UT group. Higher TLR-4 and NF-κB activation were found in LPS-stimulated monocytes of UT men concomitant with higher TNF-α production and diminished IL-10 production after heat treatment. TR individuals presented lower NF- κB activation in LPS-stimulated monocytes after heat treatment. Our data suggest that the training status of individuals may impact on the anti-inflammatory response of heat treatment.